Green Synthesis of a Molecularly Imprinted Polymer Based on a Novel Thiophene-Derivative for Electrochemical Sensing - Francesco Gagliani; Tiziano Di Giulio; Sara Grecchi; Tiziana Benincori; Serena Arnaboldi; Cosimino Malitesta; Elisabetta Mazzotta (Molecules, 2024)
An environmentally friendly and sustainable approach was adopted to produce a molecularly imprinted polymer (MIP) via electropolymerization, with remarkable electrochemical sensing properties, tested in tyrosine (tyr) detection. The 2,2′-bis(2,2′-bithiophene-5-yl)-3,3′-bithianaphtene (BT2-T4) was chosen as functional monomer and MIP electrosynthesis was carried out via cyclic voltammetry on low-volume (20 μL) screen-printed carbon electrodes (C-SPE) in ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ((BMIM) TFSI). An easy and rapid washing treatment allowed us to obtain the resulting MIP film, directly used for tyr electrochemical detection, carried out amperometrically. The sensor showed a linear response in the concentration range of 15–200 μM, with LOD of 1.04 µM, LOQ of 3.17 μM and good performance in selectivity, stability, and reproducibility. Tyrosine amperometric detection was also carried out in human plasma, resulting in a satisfactory recovery estimation. The work represents the first use of BT2-T4 as a functional monomer for the production of a molecularly imprinted polymer, with a green approach afforded by using a few microliters of a room temperature ionic liquid as an alternative to common organic solvents on screen-printed carbon electrodes, resulting in a valuable system that meets the green chemistry guidelines, which is today an essential criterion in both research and application field.